Technology Acceptance Model untuk Mengukur Persepsi Kemudahan dan Kegunaan Zahir Accounting dalam Menyusun Laporan Keuangan - Lusy Oktaviani; Syam Gunawan; Gita Cahyani Lestari (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
Current technological developments encourage companies to also use technology so that their employees can work more efficiently. That is why the Zahir Accounting application is used to help PT Nikko Utama in preparing financial reports. This study aims to measure the level of satisfaction in using the Zahir Accounting application. This study uses the Technology Acceptance Model (TAM) method to measure the satisfaction of Zahir Accounting application users. By distributing questionnaires to 30 respondents, in this study based on 4 (four) independent variables (Perceived Ease of Use, Perceived Usefulness, Attitude Toward Using, and Actual Usage) it can be explained that user satisfaction in using the Zahir Accounting application is 84.1%, so it can be said that users feel satisfied and find it easy to use the Zahir Accounting application.